<span>2x - 3y - z
Substitute the variables for the numbers provided for them
</span><span>2(-2) - 3(3) - (-2)
Multiply 2 by -2
-4 - 3(3) - (-2)
Multiply -3 by 3
-4 - 9 - (-2)
Subtract 9 from -4
-13 - (-2)
Convert Subtract -2 from -13. It would be the same as adding 2 to -13.
Final Answer: -11</span>
Let x = state b , then x + 2 = state a
now: x + (x +2) = 9090 or 2x + 2 = 9090 Solving this equation:
2x + 2 = 9090 subtract 2 from both sides
2x = 9088 divide both sides by 2
x = 4544
that means x + 2 = 4546
so state a = 4546 and state b = 4544
Answer:
swich the one attached to equation with the one attached to expression
Step-by-step explanation:
an equation need to have an equals sign, an expression doesnt.
Answer:
it is 360
Step-by-step explanation:
all you do is subtact the first number by the second number